Template-assisted synthesis of adenine-mutagenized cDNA by a retroelement protein complex. Issue 18 (11th July 2018) - Handa, Sumit; Jiang, Yong; Tao, Sijia; Foreman, Robert; Schinazi, Raymond F; Miller, Jeff F; Ghosh, Partho
Abstract: Diversity-generating retroelements (DGRs) create unparalleled levels of protein sequence variation through mutagenic retrohoming. Sequence information is transferred from an invariant template region ( TR ), through an RNA intermediate, to a protein-coding variable region. Selective infidelity at adenines during transfer is a hallmark of DGRs from disparate bacteria, archaea, and microbial viruses. We recapitulated selective infidelity in vitro for the prototypical Bordetella bacteriophage DGR. A complex of the DGR reverse transcriptase bRT and pentameric accessory variability determinant (Avd) protein along with DGR RNA were necessary and sufficient for synthesis of template-primed, covalently linked RNA–cDNA molecules, as observed in vivo . We identified RNA–cDNA molecules to be branched and most plausibly linked through 2′-5′ phosphodiester bonds. Adenine-mutagenesis was intrinsic to the bRT-Avd complex, which displayed unprecedented promiscuity while reverse transcribing adenines of either DGR or non-DGR RNA templates. In contrast, bRT-Avd processivity was strictly dependent on the template, occurring only for the DGR RNA. This restriction was mainly due to a noncoding segment downstream of TR, which specifically bound Avd and created a privileged site for processive polymerization. Restriction to DGR RNA may protect the host genome from damage. These results define the early steps in a novel pathway for massive sequence diversification.